Nxele and Ntsikana : a critical study of the religious outlooks of two nineteenth century Xhosa Prophets and their consequences for Xhosa Christian practice in the Eastern Cape - Tisani, Ezra Vuyisile (Department of Religious Studies, 2015)
Includes bibliographical references.